Anti-osteoporosis effects of osteoking via reducing reactive oxygen species. (15th November 2019) - Qin, Di; Zhang, Huijie; Zhang, Hongfei; Sun, Tongyi; Zhao, Hongbin; Lee, Wen-Hui
Abstract: Ethnopharmacological relevance: Osteoking is a Traditional Chinese Medicine consisting of seven types of medicinal herbs originated from Yi nationality and has been used in clinic to treat bone diseases for thousands of years in China. Osteoking shows excellent clinical therapeutic effects on osteoporosis, but it is not clear whether Osteoking could exhibit beneficial effects against osteoporosis via reducing reactive oxygen species (ROS). Aim of the study: To explore whether the protective effects of Osteoking on osteoporosis related to ROS, we investigated the effects of Osteoking on osteogenesis differentiation under oxidative stress. Materials and methods: The ovariectomized (OVX) osteoporosis model was established by ovarian surgery, and Osteoking was orally administrated for 84 days. Then the pathogenesis changes of femur were analyzed by Hematoxylin and eosin (H&E) and Masson's trichrome staining. The levels of ROS, malondialdehyde (MDA) and superoxide dismutase (SOD ) from rats' serum were further measured. In vitro, mouse pre-osteoblastic MC3T3-E1 cells pre-treated with or without 0.25 mM tert -butyl hydroperoxide ( t -BHP) for 2 h were cultured and treated with different dilutions of Osteoking or 20 μM N-Acetyl-L-cysteine for another 24 h, respectively. The intracellular ROS production and markers of oxidative damage of the MC3T3-E1 cells were determined using corresponding kits, respectively. The expressions of alkaline phosphatase (ALP), collagen type I, osteoprotegerin (OPG), TGF-β1, β-catenin, receptor activator of nuclear factor-κB ligand (RANKL) and interleukin-6 (IL-6) were further analyzed by qRT-PCR and western blotting upon treatment. Results: Our results showed that Osteoking significantly improving trabecular microstructure by promoting collagen fiber repair and new bone or cartilage regeneration was demonstrated in OVX osteoporosis rat models by micro-CT analysis and histological staining results. Osteoking supplementation reduced the levels of ROS and MDA in OVX rat serum and increased SOD activities. In addition, Osteoking could also up-regulate the proteins expression levels of Runx2, osteocalcin (BGP) and osteoprotegerin (OPG) but reducing the expression of tartrate-resistant acid phosphatase (TRAP). In vitro, Osteoking could effectively inhibit the t -BHP-induced intracellular excessive ROS production and protect cells from oxidative stress in mouse pre-osteoblastic MC3T3-E1 cells. Meanwhile, the mRNA expressions of ALP, collagen type I, OPG, TGF-β1 and β-catenin were also up-regulated whereas the RANKL and IL-6 were down-regulated in Osteoking-treated MC3T3-E1 cells. Conclusions: A novel therapeutic mechanism of Osteoking on osteoporosis reveals by present investigation. Clinic effects of Osteoking to treat osteoporosis are closely related to its ability to reduce oxidative stress. Graphical abstract: Image 1